The JET program for education and training at middle management level - Jorge, Ligaya C. (1977)
At the level of government middle managers, the Junior Executive Training (JET) Program seeks to promote managerial effectiveness, professionalism, dedication to the public service, and awareness of the central role of the civil service in national development programs. The program uses a critical mass strategy and a three-pronged approach to maximize the effectiveness of scarce resources. Support from top government leaders, training fees, and a training evaluation scheme are also "inputs" to JET. Initial feedbacks show that majority of Civil Service Commission (CSC) participants have favorable impressions regarding the program, e.g., achievement of course objectives and acceptability. Finally, more objective data could establish significant accomplishments of JET in terms of doctrinal achievements, improved leadership attributes, and improved resource management capability.
Keywords: Civil service -- Personnel management; Junior Executive Training Program; Public administration